2012
DOI: 10.5999/aps.2012.39.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Free Flap Reconstruction Using Anterolateral Thigh Flap Pedicle for Interposition Artery and Vein Grafts

Abstract: We experienced satisfactory outcomes by synchronously transplanting an artery and vein using an anterolateral thigh flap pedicle between the vascular pedicle and recipient vessel of a flap for scalp reconstruction. A 45-year-old man developed a subdural hemorrhage due to a fall injury. In this patient, the right temporal cranium was missing and the patient had 4×3 cm and 6×5 cm scalp defects. We planned a scalp reconstruction using a latissimus dorsi free flap. Intraoperatively, there was a severe injury to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…On the other hand, Zhao et al [37] documented the flap failure in a traumatic scalp injury 6 weeks after surgery and performed a rescue procedure based on retrograde blood flow of contralateral superficial temporal artery. Park et al [38] considered reconstruction of the cranial profile after traumatic injury with a chimeric ALT flap with no complications by using facial artery and vein in anastomosis. Llorente et al [39] described the use of different free flaps in skull base, including the chimeric ALT flap; the rate of complication for each type of flap and which kind of defect was repaired with chimeric ALT flap was not reported.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…On the other hand, Zhao et al [37] documented the flap failure in a traumatic scalp injury 6 weeks after surgery and performed a rescue procedure based on retrograde blood flow of contralateral superficial temporal artery. Park et al [38] considered reconstruction of the cranial profile after traumatic injury with a chimeric ALT flap with no complications by using facial artery and vein in anastomosis. Llorente et al [39] described the use of different free flaps in skull base, including the chimeric ALT flap; the rate of complication for each type of flap and which kind of defect was repaired with chimeric ALT flap was not reported.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…10,11 Several plastic surgeons also used it as an interposition graft in scalp and lower extremity reconstruction. 12,13 Despite anatomic inconstancy, the anterolateral thigh free flap is relatively easy to harvest and utilize. Except for the case of 9.1% in which the perforators originate only from a transverse branch of the lateral femoral circumflex artery, 14 its pedicle can be used to bridge a vascular defect in the extremity.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Several plastic surgeons also used it as an interposition graft in scalp and lower extremity reconstruction. 12,13…”
Section: Discussionmentioning
confidence: 99%
“…Emergency situations, such as rare vascular variations, intravascular thrombosis, and vessel injury during dissection, can be perplexing. Vein grafting is the most commonly used method when such situations arise, but it causes additional donor site morbidity (Park et al, ). Lee et al suggested selection of the most distal perforator, eccentric flap placement, and proximal de‐epithelisation in ALT flaps (Lee, Chen, Chou, & Shieh, ).…”
Section: Discussionmentioning
confidence: 99%